SUBJECTIVE EXPERIENCE AND OBJECTIVE MEASUREMENT: INTEGRATING NEWTON'S LAWS AND SMARTPHONE SENSORS IN PHYSICS LEARNING - Nurul Fitria; Ishafit; Okimustava; Fida Afifah; Sri Wahyuni; Ermelinda; Zellius Ragiliawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In today’s digital era, physics education demands more contextual and technology-integrated approaches to bridge abstract concepts with real-world experiences. This study aims to develop an innovative approach in physics learning by utilizing smartphone sensors to analyze the vertical motion dynamics of an elevator based on Newton’s Laws. The experiment was conducted in a five-story elevator at BRIDA Surakarta using the Phyphox application, which employs the smartphone’s built-in accelerometer and barometer. The modes "acceleration without g" and "elevator" were used to record real-time data of acceleration, velocity, and altitude. Data was collected through ten trials—five upward and five downward motion cycles. The recorded data revealed maximum acceleration values of ±8 m/s², aligning with the typical operational range of elevators (6–10 m/s²), while the altitude change was approximately ±18 meters, corresponding to the actual height of the building. The elevator’s motion was clearly segmented into three phases: initial acceleration, constant velocity, and deceleration. In each phase, passengers experienced distinct physical sensations—from feeling pressed down, to normal, to weightless—which closely correlated with the recorded acceleration data. These findings strongly validate the application of Newton’s Laws in non-inertial systems and the alignment between subjective sensations and quantitative measurements. Beyond reinforcing conceptual understanding through firsthand experience, this approach encourages active student engagement and enables experimentation without reliance on conventional physics laboratories. The study affirms that smartphone-based technologies hold great potential in democratizing access to scientific instrumentation and enhancing the quality of STEM education in a contextual, inclusive, and applicable manner.